Investigating number of children with disabilities in HUSM registry and level of participation in physical activities: a pilot study - Bakri, Rafidah (Universiti Sains Malaysia, 2013)
Currently, number of children with disabilities in Malaysia was only based on estimation by World Health Organization (WHO). Besides, they are more likely to be sedentary, placing them at higher risk of associated health condition than normal children. The purpose of this study was to investigate the number of children with disabilities in the Hospital USM registry throughout 2011 and levels of participation of children with physical disabilities in physical activities. Number of children with disabilities was obtained by accessing the HUSM registry system and were categorized according to the International Statistical Classification of Diseases and Related Health Problems (ICD-10). Subsequently, 35 respondents with physical disabilities were randomly selected to investigate their level of participations in physical activities.Data for physical activities was collected using translated version of Physical Activity Questionnaire for Children (PAQ-C) and analyzed using the SPSS 20.0 software. Descriptive analysis was performed to investigate the number of children with disabilities in the Hospital USM registry. Independent T-Test was performed to analyze mean difference of the physical activity score between genders as well as between those who attend rehabilitation intervention and not attend. One-way ANOVA was performed to analyze mean difference of physical activity score between family incomes as well as between types of disabilities. Present study found that there were a total of 898 children with disabilities that have been admitted into the Hospital USM from 1st January until 31st December 2011 and 1121 infants categorized as high risk baby. All 35 respondents in this study had low mean physical activity score. This indicated that participation of children with physical disabilities in physical activities was generally low. The test result also revealed that there is no significant difference of level of participation in physical activities between gender. rehabilitation services, as well as family income (p>0.05). But there is significant difference in level of participation in physical activities between type of disabilities (p=0.003).